2015
DOI: 10.4142/jvs.2015.16.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and functional analysis of the duck Toll-like receptor 5 (TLR5) gene

Abstract: Toll-like receptor 5 (TLR5) is responsible for the recognition of bacterial flagellin in vertebrates. In the present study, the first TLR5 gene in duck was cloned. The open reading frame (ORF) of duck TLR5 (dTLR5) cDNA is 2580 bp and encodes a polypeptide of 859 amino acids. We also cloned partial sequences of myeloid differentiation factor 88, 2'-5'-oligoadenylate synthetase (OAS), and myxovirus resistance (Mx) genes from duck. dTLR5 mRNA was highly expressed in the bursa of Fabricius, spleen, trachea, lung, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It was further detected that NDV-derived dsRNA colocalizes with TLR3 in subcellular structures, and the activation of TLR3 and TLR7 is associated with the NF-κB pathway of innate immune responses, proving the monitoring role of the TLRs against NDV infection [54]. Apart from TLR3 and TLR7, the overexpression of duck TLR5 in DF-1 and HeLa cells also initiated the NF-κB pathway and upregulated IL-6 promoter activities [57]. In geese, TLR1, TLR3, TLR5, TLR7, and TLR15 expressions were all upregulated after NDV genotype VIId strain infection, suggesting that these TLRs may also participate in anti-NDV responses, which needs further exploration [45].…”
Section: Receptors For Ndv Pampmentioning
confidence: 90%
“…It was further detected that NDV-derived dsRNA colocalizes with TLR3 in subcellular structures, and the activation of TLR3 and TLR7 is associated with the NF-κB pathway of innate immune responses, proving the monitoring role of the TLRs against NDV infection [54]. Apart from TLR3 and TLR7, the overexpression of duck TLR5 in DF-1 and HeLa cells also initiated the NF-κB pathway and upregulated IL-6 promoter activities [57]. In geese, TLR1, TLR3, TLR5, TLR7, and TLR15 expressions were all upregulated after NDV genotype VIId strain infection, suggesting that these TLRs may also participate in anti-NDV responses, which needs further exploration [45].…”
Section: Receptors For Ndv Pampmentioning
confidence: 90%
“…TLR, a group of conserved type I transmembrane proteins, is one of the most critical PRRs which can sense the different invading pathogens outside the cell membrane and internally in endosomes and lysosomes. Currently, 10 TLR have been reported in human, and 10 TLR in chicken, while only 5 TLR (TLR 2 [ 62 ], TLR3 [ 63 ], TLR4 [ 64 ], TLR5 [ 65 ], and TLR7 [ 66 ]) in duck. Furthermore, there are some differences between avian and mammal TLR, including the absence of TLR8 and TLR9 and the presence of TLR1La, TLR1Lb, TLR15, and TLR21 in chickens [ 67 , 68 ].…”
Section: Dtmuv Infection Triggers Host Innate Immune Responsesmentioning
confidence: 99%
“…To date, 6 duck (Anas platyrhynchos) TLRs (duTLRs), duTLR1 (Huang et al, 2011), duTLR2 (Huang et al, 2011), duTLR3 (Jiao et al, 2012), duTLR 4 (Jia et al, 2012), duTLR5 (Cheng et al, 2015), and duTLR7 (MacDonald et al, 2008) have been identified. However, most components of the TLR pathway of duck remain elusive, including the MyD88 key adaptor protein coordinating the Toll pathway.…”
Section: Discussionmentioning
confidence: 99%